Alchemy beneath Poetry: Ibn Arfaʿ Raʾs’s Rhyme in khāʾ - Díaz-Fajardo, Montse (Oriens, 2025)
We present a critical edition, translation, and commentary of the Rhyme in khāʾ found in Shudhūr al-dhahab (Shards of gold) by the Andalusī Ibn Arfaʿ Raʾs (fl. twelfth century). The extraordinary number of preserved manuscripts of Shudhūr al-dhahab (over a hundred) is probably due to the value of this work in two fields, alchemy and poetry, as alluded to in the name given to Ibn Arfaʿ Raʾs: ‘the poet of scientists, and the scientist of poets’/shāʿir al-ḥukamāʾ wa-ḥakīm al-shuʿarāʾ. Our study investigates the aesthetic poetic creation and the alchemical subjects proposed in the Rhyme in khāʾ.